Cell culture pO2 monitoring with a fiber optic oxygen sensor - Liu, J; Wang, C; Zeng, Y; Yang, C; Li, H; Fan, H; Hahn, C; Farmery, A; Chen, R (IOP Publishing, 2016)
We report the monitoring of oxygen partial pressure (pO2) in the liquid phase in cell cultures with a luminescence quenching based fiber optic oxygen sensor. The sensitivity of the fiber optic oxygen sensor was evaluated in the gas phase and the sensor was calibrated in the liquid phase before monitoring cell culture pO2 with a luminescence phase detection system. In these experiments, porcine kidney (PK-15) cells were used as the cell samples and the experimental results showed that the sensor is suitable for monitoring of pO2 in gas and liquid phases. In addition, we found that in cell cultures exposed to ambient air, measured pO2 values in the liquid phase differed according to the different cell densities in the culture. Under conditions of low pO2 in the gas phase and high cell density, the cell metabolism reduces the pO2 in the liquid phase to values lower than those of the gas headspace, indicating that the cellular oxygen uptake rate exceeds the oxygen diffusion rate. Therefore there is a need for direct pO2 monitoring in a cell culture, particularly in static high density cell culture systems where oxygen mass transfer is limited.